Primary cervical signet ring cell carcinoma: A rare case report and literature review - Ezgi Oktay; Mürşide Çevikoğlu Kıllı; Gözde Arslan; Görkem Ülger; Tolgay Tuyan İlhan (Elsevier, 2024)
Introduction: Signet-ring cell carcinoma of the uterine cervix commonly occurs owing to metastasis. Today, the rarity of primary cervical origin is still making it a diagnostic challenge. This review aims to raise awareness to maintain early diagnosis and appropriate management. Case Presentation: A 37-year-old patient presented with postcoital vaginal bleeding with a history revealing a negative Papanicolaou smear 2 years prior. Pelvic examination revealed a cervical mass and the biopsy was interpreted as a signet ring cell pattern. Detailed extrapelvic evaluation was made to rule out a possible extragenital primary tumor. The patient underwent a type-2 radical hysterectomy, pelvic and paraaortic lymphadenectomy. Following the histopatologic evaluation, the case was diagnosed and managed as primary cervical signet ring cell carcinoma (PCSRCC) with International Federation of Gynecology and Obstetrics 2018 stage IIIC. The patient received adjuvant chemoradiotherapy and is currently disease-free 24 months following surgery. Discussion: The small number of cases causes difficulty with an accurate diagnosis. Imaging and immunohistochemical (IHC) studies should be performed to distinguish possible primary sites. IHC studies are not yet close to refusing or confirming the diagnosis. Due to the lack of data, there is no consensus on the proper therapeutic strategy. Prognosis and survival appear to depend upon the stage of disease at diagnosis. Therefore, the awareness of such a histopathological kind of cervical cancer is crucial.